FINDINGS ON THE TRAINING CLASSES OPTIMIZE STARTING FOOTBALL - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Evolution football game, which in recent decades has experienced a high level of progress at a speed game much improved, and possession of the ball as prolonged requires training future players since the earliest ages, so selection and training from the age of 5-6 years. To address the scientific selection and training of children is necessary to know, studying and highlighting the player's performance profile of high performance, structured models to be attained during instruirii.La this age without previously accumulated a minimum of technical knowledge - tactice with characteristic entiziasmul childhood students will turn the game into a cluster continues around the ball, there is collaboration, which will not allow learning proper basic technical elements and will contribute decisively sometimes, loss of pleasure practice this sport. In this respect, rehearse separate elements and basic techniques, individually, in pairs or small groups of students in the form of static exercises, easy dynamic of relays with different degrees of complexity, depending elevilor.Jocurile of the ball must supplement this means, have simplified rules and a predominantly playful.